Attitude of health care workers to patients and colleagues infected with human immunodeficiency virus - Ayebo E Sadoh; Wilson E Sadoh; Adeniran Olubukola Fawole; Ayo Oladimeji; Oladapo Sotiloye (Taylor & Francis Group, 2009)
Discrimination against persons living with HIV/AIDS in hospital settings has been documented. This study examined the attitude of health care workers (HCWs) to nurses, doctors and patients infected with HIV. A total of 345 respondents selected by multistage sampling techniques were surveyed, using a semi-structured questionnaire, which explored respondents' attitude to HIV-infected patients and colleagues with HIV/AIDS. HCWs were unwilling to accept that medical procedures be carried out on them by HIVinfected doctors and nurses, with almost 80% refusing surgery or assistance at surgery on them by an HIV-infected doctor or nurse. They were also significantly more unwilling to accept that medical procedures be carried out on them by an infected colleague, compared with their carrying out the same procedure on an HIV-infected patient. Thus, HCWs seemed to believe that the risk of contracting HIV was higher if an infected HCW were to perform medical procedures on them, and fear of contracting HIV seemed to be the driving force for their negative attitudes. Education on occupational risks of HIV, provision of a safe working environment with enforcement of universal precautions, as well as provision of post-exposure prophylaxis are suggested as ways to enable HCWs to change their attitudes.